2005
DOI: 10.1038/nature03631
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal display of PfEMP-1 on erythrocytes carrying haemoglobin C may protect against malaria

Abstract: Haemoglobin C, which carries a glutamate-to-lysine mutation in the beta-globin chain, protects West African children against Plasmodium falciparum malaria. Mechanisms of protection are not established for the heterozygous (haemoglobin AC) or homozygous (haemoglobin CC) states. Here we report a marked effect of haemoglobin C on the cell-surface properties of P. falciparum-infected erythrocytes involved in pathogenesis. Relative to parasite-infected normal erythrocytes (haemoglobin AA), parasitized AC and CC ery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
175
1
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(188 citation statements)
references
References 28 publications
8
175
1
4
Order By: Relevance
“…A polymorphism resulting in erythrocyte complement receptor (CR) 1 deficiency that is found at high frequency in Melanesian populations exposed to malaria is associated with reduced P. falciparum rosetting (spontaneous binding of infected erythrocytes to uninfected erythrocytes) (3) and protection against severe disease (4). The protective effects of thalassemia, sickle cell trait, and HbC may also be partly caused by reduced rosetting (5,6). Rosetting is a known parasite virulence factor (7,8) that is thought to contribute to the pathogenesis of severe malaria by obstructing microvascular blood flow (9).…”
mentioning
confidence: 99%
“…A polymorphism resulting in erythrocyte complement receptor (CR) 1 deficiency that is found at high frequency in Melanesian populations exposed to malaria is associated with reduced P. falciparum rosetting (spontaneous binding of infected erythrocytes to uninfected erythrocytes) (3) and protection against severe disease (4). The protective effects of thalassemia, sickle cell trait, and HbC may also be partly caused by reduced rosetting (5,6). Rosetting is a known parasite virulence factor (7,8) that is thought to contribute to the pathogenesis of severe malaria by obstructing microvascular blood flow (9).…”
mentioning
confidence: 99%
“…Ceux en cause dans la protection de l'hôte ont fait l'objet d'études multiples [7] : ils ont majoritairement ciblé l'HbS, dont l'impact en santé est majeur en Afrique, mettant en évidence chez les hétérozygotes AS plusieurs mécanismes de protection : diminution de l'invasion parasitaire des GR, moindre formation de rosettes et modification de l'adhérence des érythro-cytes AS infectés à l'endothélium [10]. Concernant l'HbC, on a montré une moindre expression de l'antigène PfEMP-1 du parasite modifiant l'adhérence à la paroi vasculaire de globules rouges porteurs de cette hémoglobine [11]. Ces mécanismes concernent tous les formes parasitaires asexuées, mais en revanche, on sait peu de choses sur la façon dont le génotype HBB pourrait influencer la formation des gamétocytes en fin de cycle asexué chez l'hôte.…”
Section: Infectivité Comparée De L'hôte Selon Son Génotype Hbbunclassified
“…This is further supported by evidence of a positive selection, 9,10 and by in vitro studies with human cells. [11][12][13][14] Although the molecular mechanisms behind the protection remain to be elucidated, several mechanisms have been proposed: (i) a low capacity of the parasite to replicate in red blood cells; (ii) an altered expression of parasite antigens on the surface of red blood cells leading to a diminished cytoadhesion and/or an altered immune response; (iii) and an increased phagocytosis of the infected red blood cells. Several studies have demonstrated in vitro that the growth of the parasite was inhibited in CC cells, [12][13][14] whereas the parasite grows normally in AC cells.…”
Section: Introductionmentioning
confidence: 99%